Halal industry as a Catalyst for economic growth - Wan Sulaiman, Wan Syibrah Hanisah; Jaiyeoba, Haruna Babatunde (AIJR Publisher, 2025)
The halal industry, which offers a unique combination of Shariah-compliant principles, ethical norms, and sustainable practices, has emerged as a significant driver of economic growth in developing countries. In examining the halal industry as a catalyst for economic progress in these nations, this study explores the industry’s multifaceted contributions to economic development, its alignment with SDG 8 on Decent Work and Economic Growth, and its untapped potential to address economic challenges. The study emphasises that by leveraging its various sectors, developing countries can capitalise on the halal industry’s potential for growth and development. Having reviewed pertinent literature, the study identifies several opportunities for developing countries to harness the halal industry, including enhanced domestic consumption, import substitution, and integration into global supply chains. It also highlights strategic recommendations for policymakers and industry stakeholders, such as investing in halal certification systems, human capital development, digital innovations, and infrastructure for halal logistics and supply chains. Furthermore, the study advocates for inclusive and sustainable growth models that encourage rural and marginalised communities to benefit from the industry’s expansion. While the research provides theoretical insights into the halal industry’s potential, it acknowledges the need for empirical studies to validate and extend this discussion. Ultimately, the research positions the halal industry as a pivotal tool for achieving sustainable economic growth and aligning developing countries with global market trends.